The ADH7 Promoter of Saccharomyces cerevisiae is Vanillin-Inducible and Enables mRNA Translation Under Severe Vanillin Stress - Nguyen, Trinh T. M.; Iwaki, Aya; Izawa, Shingo (Frontiers in Microbiology, 2015)
Vanillin is one of the major phenolic aldehyde compounds derived from lignocellulosic biomass and acts as a potent fermentation inhibitor to repress the growth and fermentative ability of yeast. Vanillin can be reduced to its less toxic form, vanillyl alcohol, by the yeast NADPH-dependent medium chain alcohol dehydrogenases, Adh6 and Adh7. However, there is little information available regarding the regulation of their gene expression upon severe vanillin stress, which has been shown to repress the bulk translation activity in yeast cells. Therefore, in this study, we investigated expression patterns of the ADH6 and ADH7 genes in the presence of high concentrations of vanillin. We found that although both genes were transcriptionally upregulated by vanillin stress, they showed different protein expression patterns in response to vanillin. Expression of Adh6 was constitutive and gradually decreased under vanillin stress, whereas expression of Adh7 was inducible, and, importantly, occurred under severe vanillin stress. The null mutants of ADH6 or ADH7 genes were hypersensitive to vanillin and reduced vanillin less efficiently than the wild type, confirming the importance of Adh6 and Adh7 in vanillin detoxification. Additionally, we demonstrate that the ADH7 promoter is vanillin-inducible and enables effective protein synthesis even under severe vanillin stress, and it may be useful for the improvement of vanillin-tolerance and biofuel production efficiency via modification of yeast gene expression in the presence of high concentrations of vanillin.